Measurements and modeling of absorptive partitioning of volatile organic compounds to painted surfaces. (6th March 2020) - Algrim, Lucas B.; Pagonis, Demetrios; de Gouw, Joost A.; Jimenez, Jose L.; Ziemann, Paul J.
Abstract: Partitioning to surfaces is an important sink for volatile organic compounds (VOCs) indoors, but the mechanisms are not well understood or quantified. Here, a mass spectrometer was coupled to a portable surface reactor and a flow tube to measure partitioning of VOCs into paint films coated onto glass or wallboard, and their subsequent diffusion. A model was developed to extract values of the effective absorbing organic mass concentration of the film, Cw, which is a measure of absorption capacity, and VOC diffusion coefficients, Df, from VOC time profiles measured during film passivation and depassivation. Values of Cw agreed well with the value estimated from the paint film mass and flow tube air volume, and Df values (also measured using attenuated total reflectance‐Fourier transform infrared spectroscopy) correlated well with VOC vapor saturation concentrations, C *, estimated using a group contribution method. The value of these relationships for estimating key parameters that control VOC partitioning into paint and the fate of VOCs indoors was demonstrated using a house model, which indicated that >50% of VOCs with C * ≤10 8 μg/m 3 ( C * of octane, hexanone, and propanol) that contacted a paint film of typical thickness fully permeated the film regardless of emission duration.